Global burden of cardiovascular disease mortality attributable to secondhand smoke, 1990-2019: Systematic analysis of the Global Burden of Disease Study 2019. - Juan Dong; Xumin Ma; Xingxin Hu; Mengmeng Yan (PLoS ONE)
Background Few studies have globally assessed the cardiovascular disease (CVD) mortality burden attributable to secondhand smoke. We aimed to address this research gap. Methods We used a systematic analysis design using data from the Global Burden of Disease Study 2019. Our primary outcome measures were the age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life years (DALYs) for CVD attributable to secondhand smoke. The annual average percentage change (AAPC) was utilized to describe the temporal trends of ASMR and DALYs. Results From 1990 to 2019, global ASMR for CVD due to secondhand smoke decreased from 11.45 (95% CI: 9.47 to 13.42) to 7.43 (95% CI: 6.09 to 8.85), and DALYs decreased from 274.12 (95% CI: 225.36 to 322.20) to 176.93 (95% CI: 145.21 to 211.28). ASMR and DALYs attributable to secondhand smoke are on the rise in 47 countries, with 18 of these countries experiencing increases across both genders and all cardiovascular subtypes. Uzbekistan, Lesotho, and the Philippines have the highest AAPC for CVD due to secondhand smoke in ASMR and DALYs. Specifically, Uzbekistan's overall ASMR AAPC is 2.2 (95%CI: 2.1-2.3), Lesotho's is 1.3 (95%CI: 1.2-1.3), and the Philippines' is 1.1 (95%CI: 1.0-1.2). In terms of DALYs, the AAPC values are 1.7 for Uzbekistan (95%CI: 1.7-1.8), 1.4 for Lesotho (95%CI: 1.3-1.5), and 1.8 for the Philippines (95%CI: 1.7-1.9). Conclusion Over the past three decades, the epidemiological landscape of CVD mortality associated with secondhand smoke has undergone significant shifts. Notwithstanding global advancements, intensified interventions are paramount in regions experiencing ascending rates.